The EDUKASI DAMPAK PERILAKU TINDAKAN TIDAK AMAN PADA KARYAWAN BAGIAN PRODUKSI DI PT. ADEI CRUMB RUBBER INDUSTRY - Ginting, Evfy Septriani (Jurnal Pengabdian Masyarakat Putri Hijau, 2024)
W.H Heinrich stated that 88% of workplace accidents are caused by unsafe acts. Employment tenure refers to the period of time an employee works in a particular place. Attitude is an individual's tendency to respond in a specific way to stimuli. Unsafe behavior is human behavior that deviates from proper work procedures, thereby endangering oneself. The purpose of this outreach program is to provide education on the impact of unsafe behavior to workers at PT Adei Crumb Rubber Industry. Consequently, the expected outcome of this counseling is for the workers at PT Adei Crumb Rubber Industry to work with safe behavior to avoid accidents and work-related illnesses, as well as to enhance the company's role in implementing a safety culture (K3).